Kepuasan sebagai mediasi pengaruh brand image, service quality dan experiential marketing terhadap loyalitas nasabah - Awalia, Sofi Nur; Setiawan, Ari (Journal of Management and Digital Business, 2022)
This study analyzed the effect of brand image, service quality, and experiential marketing on customer loyalty at PT Bank Tabungan Negara Syariah Solo, with satisfaction as an intervening variable. This type of research is quantitative by applying a purposive sampling technique to the number of samples, 100 respondents. Furthermore, data collection was carried out by distributing Likert-scale questionnaires. The analytical method uses path analysis. The study's results prove that brand image has a positive but insignificant effect on customer satisfaction. In contrast, service quality and experiential marketing positively and significantly affect customer satisfaction. Each variable, namely brand image, service quality, experiential marketing, and customer satisfaction, positively and significantly influences loyalty. However, the variable of customer satisfaction was unable to facilitate the influence of brand image, service quality, and experiential marketing on customer loyalty.